A Chip Off the Old Block? The Relationship of Family Factors and Young Adults’ Views on Aging - Hoffmann, Cathy; Kornadt, Anna E. (Frontiers in Psychology, 2022)
Views on aging (VoA), such as self-perceptions of aging or age stereotypes are generated in early childhood and continue to develop throughout the entire lifespan. The ideas a person has about their own aging and aging in general influence their behavior toward older persons as well as their own actual aging, which is why VoA are already important in adolescence and young adulthood. The current study investigates VoA of young adults in different domains (continued growth, physical decline, social loss) and how different family aspects are related to VoA. From February to March 2021, N = 305 young adults [aged 18–30 years, Mage(SD) = 22.20 (2.60)] participated in an online survey, in which, in addition to sociodemographic variables and family aspects (contact with grandparents, family age climate, i.e., the frequency and valence of talking about age in the family), self-perceptions of aging, age stereotypes, and the young adults’ ratings of their parents’ VoA were assessed. The results of stepwise regression analyses predicting the young adults’ VoA, revealed significant associations between the quality of contact with grandparents and the self-perceptions of aging of young adults. However, the frequency of contact was neither related to young adults’ self-perceptions of aging nor age stereotypes. Grandparents’ health status emerged as a significant moderator between the relationship of contact quality and the young adults’ self-perceptions of aging as continued growth and physical decline. Family climate was also found to be significantly related to young adults’ self-perceptions of aging. Similarities regarding VoA within the family were demonstrated, based on proxy report from the respondents. The results underline the importance of family aspects for the development of VoA in young adulthood, and the significance of interventions targeting these factors to combat ageism.